Development and Characterization of Ultrasound-assisted PLGA Nanobubbles for the Triggered Delivery of Pemigatinib by Design of Experiments (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
This study used a central composite design (CCD) to evaluate how the independent attributes—sonication distance (X1), amplitude (X2), time (X3), & power (X4)—impacted two outcomes—droplet-size (Y1) & polydispersity index (PDI) (Y2). With the time-consuming & inefficient "changing one factor at a time" approach would have been an option for this multifactor optimization, but we opted against it since we wanted to be sure we had the best possible values. Here, a mathematical model of the combined influence of the processing elements led to the selection of a CCD, which is known to be significantly more dependable. Using a double emulsion technique, we created and fine-tuned a drug delivery system consisting of nanobubbles loaded with pemigatinib. Pemigatinib nanobubbles were studied for their shape, surface charge, and particle size to determine their physicochemical characteristics and found that they were spherical with the Zeta potential (ZP) and particle size of -25.3±2.98 & 38.53±2.14 respectively. Pemigatinib-loaded nanobubbles were also tested for their release behaviors and drug encapsulation effectiveness. Finally, we tried to study the anti-tumor activity and cellular absorption of poly (lactic-co-glycolic acid) nanobubbles-Pemigatinib in vitro.